The fire next time - Baldwin, James, 1924-1987.; Martin, Jesse L. (North Kingstown, RI : BBC Audiobooks America, 2008)
A plea and a warning to citizens to examine the actual state of America after a century of emancipation.
Read by Jesse L. Martin.
Unabridged.
Compact discs.
Keywords: African Americans; United States -- Race relations; Black Muslims; Audiobooks